The model of cultural turn in Iranian political sociology in the last two decades - Mahsa Puladi; Hossein Harsij; Amir Masoud Shahram Nia (رهیافتهای سیاسی و بین المللی)
Political sociology has experienced many changes throughout history, and the latest example of these changes is the cultural turn. The cultural turn in political sociology may not be the same in all societies and may differ from one society to another. The article seeks to show to what extent the cultural turn in Iran's political sociology has occurred in the last two decades and what components it depends on. If a cultural turn has occurred in Iran's political sociology, to what extent does political and social construction contribute to it? The data of this research has been collected by using various new theories, semi-structured interviews, expert questionnaires, writing slips from texts and documents. Also, the fuzzy Delphi technique is used as the methodological framework of the article. The evaluations showed that the cultural turn in Iran has occurred and 21 components have been identified. These components can be used as a model in measuring the degree of cultural turn in Iran's political sociology. If we consider political sociology as the relationship between government and social construction, 20 of the 21 identified components are related to social construction and 1 component is related to political construction. The results of the research show that in Iran's political sociology, the fundamental change and transformation that happened was in the social structure and the political structure did not undergo fundamental changes.